Background concentrations of Argon-39 in shallow soil gas. (March 2021) - Fritz, B.G.; Alexander, T.R.; Johnson, C.M.; Mace, E.K.; Milbrath, B.D.; Hayes, J.C.
Abstract: While radioisotopes of noble gases are known to be indicators of underground nuclear explosions (UNE), McIntyre et al. (2017) was the first to report the presence of 39 Ar in shallow soil gas in association with a decades old UNE. While this finding hinted at the potential application of 39 Ar to be used as an indicator of a UNE, doing so would also require an understanding of the natural concentrations of 39 Ar present in soil gas. Without knowing the expected range and variability of naturally occurring concentrations of 39 Ar, it is difficult to determine what measured concentrations would be indicative of an elevated concentration. This paper presents results from 16 soil gas samples and three atmospheric air samples collected from various locations across the western United States. Shallow soil gas samples were collected into self-contained underwater breathing apparatus (SCUBA) tanks using a custom-built soil gas sampling system and then processed and analyzed for 39 Ar. The measured concentrations of 39 Ar varied from atmospheric air concentrations to about 3.5 times atmospheric air concentrations (58 mBq/m 3 ). The results presented here represent the first measurements of natural background 39 Ar concentrations in shallow soil gas. This data will be necessary if 39 Ar is to be used as an indicator of UNE. Highlights: Measurements of concentrations of 39 Ar in shallow soil gas samples and atmospheric air. Results are, to the best of our knowledge, first published concentrations of naturally occurring 39 Ar in shallow soil gas. Results compared to previously published concentrations of 39 Ar is soil gas measured near an underground nuclear explosion.